PENGARUH AUDIT TENURE DAN PREDIKSI KEBANGKRUTAN TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN SUBSEKTOR TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BEI TAHUN 2015-2020 - Nevins Andrews Henryson; Remista Simbolon (Jurnal Ekonomis, 2021)
This study aims to assess and examine the effect of tenure audits anddestruction on going-concern audit opinions. This test uses a sample of companies inthe transportation and logistics sub-sector listed on the IDX and their financialstatements have been audited for the 2015-2020 period. The author uses purposivesampling and the number of samples in this study were 84 samplesfrom 14 companies.This study uses a quantitative descriptive method and in testing the hypothesis using alogistic test. Based on the results of the research that has been carried out, it is foundthat: The results of this study indicate that tenure and bankruptcy audits have nosimultaneous effect on going concern audit opinions. Partially, the audit tenure has nosignificant effect on the going-concern audit opinion. on the other hand, the destructionthat has a significant effect on going concern audit opinion.